Evaluasi Fertilitas, Daya Tetas, Dan Karakteristik Perilaku Mengeram Induk Ayam Kampung Dalam Sistem Penetasan Alami - Sinabang, Maria Kristina; Pamungkas, Aditya (CV. SINAR HOWUHOWU, 2025)
Native chicken (Gallus gallus domesticus) is one of the local poultry species that plays an important role in providing animal protein in Indonesia. Despite their adaptability and preferred product quality, the reproductive performance of native chickens remains lower compared to commercial breeds. This study aimed to analyze hatching performance and brooding behavior of native chickens under semi-intensive management systems. A total of 10 hens aged 10–12 months and 50 eggs were observed under natural incubation. Parameters measured included fertility, hatchability, embryonic mortality, chick weight, hatch quality index, incubation period, and maternal brooding behavior. The results showed a fertility rate of 82%, hatchability of 68%, embryonic mortality of 14%, average day-old chick weight of 32.4 g with a hatch quality index of 72%, and an average incubation period of 21 days. Hens with consistent brooding behavior exhibited higher hatchability (72%) compared to less consistent hens (60%). These findings highlight that brooding behavior plays a crucial role in the success of natural incubation. Although native chickens have lower hatching performance than commercial breeds, their strong brooding instinct remains a valuable genetic trait for local poultry breeding programs.